2023
DOI: 10.1038/s41467-023-39014-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-chiral materials comprising metallosupramolecular and covalent helical polymers containing five axial motifs within a helix

Abstract: Supramolecular and covalent polymers share multiple structural effects such as communication mechanisms among monomer repeating units, which are related to their axial helical structure. Herein, a unique multi-helical material combining information from both metallosupramolecular and covalent helical polymers is presented. In this system, the helical structure described by the poly(acetylene) (PA) backbone (cis-cisoidal, cis-transoidal) guides the pendant groups in a fashion where a tilting degree emerges betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Thus, the allene group not only functions as a helix inductor due to its intrinsic chirality, but creates a supramolecular array within the helical scaffold of the polymer, generating yet another chiral motif, previously observed only for nonchiral planar spacers as OPEs or bispyridyldichlorido Pt(II) complexes. 40,41 Consequently, five different axial motifs are found in a PAEPA: the allene, the internal helix, the external helix and two allene axial arrays (P allene , M int /P ext /P axial-1 /P axial-2 ) (Figure 5d). Finally, to further demonstrate that the dynamic behavior of poly-(P)-1 is due to variations in the conformational composition of side chain c containing the sulfonamide group, a titration with different anions such as N 3 − , CN − , and F − (introduced as tetrabutylammonium salts: TBAN 3 , TBACN, TBAF, 0.35 mM in MeCN) were added to 1,2-DCE solutions of poly-(P)-1 slowly cooled at 268 K whose side chain c adopted, consequently, a bent conformer (Figure 6 for TBAN 3 and Sections 16 and 17 of the Supporting Information for other salts).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the allene group not only functions as a helix inductor due to its intrinsic chirality, but creates a supramolecular array within the helical scaffold of the polymer, generating yet another chiral motif, previously observed only for nonchiral planar spacers as OPEs or bispyridyldichlorido Pt(II) complexes. 40,41 Consequently, five different axial motifs are found in a PAEPA: the allene, the internal helix, the external helix and two allene axial arrays (P allene , M int /P ext /P axial-1 /P axial-2 ) (Figure 5d). Finally, to further demonstrate that the dynamic behavior of poly-(P)-1 is due to variations in the conformational composition of side chain c containing the sulfonamide group, a titration with different anions such as N 3 − , CN − , and F − (introduced as tetrabutylammonium salts: TBAN 3 , TBACN, TBAF, 0.35 mM in MeCN) were added to 1,2-DCE solutions of poly-(P)-1 slowly cooled at 268 K whose side chain c adopted, consequently, a bent conformer (Figure 6 for TBAN 3 and Sections 16 and 17 of the Supporting Information for other salts).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, our group reported that the use of rigid and planar spacers such as oligophenylenethynylenes (OPEs) or bispyridyldichlorido Pt­(II) complexes between the polyene backbone and the chiral pendant , can produce, in certain scaffolds, a new chiral axial arrangement of the spacers within the helical scaffold whose ECD pattern dominates the ECD spectra of the whole helical system. In these polymers, helix induction in the polyene backbone follows a chiral harvesting mechanism, where chiral information from the axial array of the spacer is harvested by the polyene backbone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations